MASTERCLASS ON DIABETES IN PREGNANCY – ‘NAVIGATING THE CURVES’ - Shah, Fatimah Zaherah Mohamed; Warman, Nur ‘Aini Eddy; Awang, Mohd Hazriq; Mohamed, Aimi Fadilah; Abdul Ghani, Rohana (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
Introduction. The incidence of diabetes mellitus (DM) in Malaysia is increasing exponentially, particularly in the younger, childbearing population. Notably, the rapid increase in the number of cases with diabetes in pregnancy in recent years has added tremendous burden to healthcare costs. DM in pregnancy has risks to both the mother and neonate, leading to intergenerational health concerns. This program aimed to disseminate information regarding the burden and approach to DM in pregnancy, as well as to educate healthcare providers to manage the condition in a comprehensive manner. Method. This diabetes in pregnancy masterclass was targeted for healthcare-workers at all levels, from students and nurses to medical-officers and specialists. This novel program focused on a multidisciplinary approach, bringing together healthcare-practitioners from varying intersected specialties; namely endocrinology, obstetrics-&-gynaecology(O&G), paediatrics and primary-care. Results. This innovative program attracted 58 participants from various specialties and diverse training levels. Program structure: This masterclass highlighted the burden of DM in pregnancy, with focus on diagnosing this condition at different healthcare levels, delivered by endocrinologists. This was followed by an O&G session on management during pregnancy, and subsequently a comprehensive approach to neonatal handling by a paediatrician. The second part of this masterclass focused on specialized management of DM in pregnancy, encompassing treatment and monitoring. A special feature of this masterclass was then conducted, with a panel discussion on challenging clinical cases, with active involvement from the participants. Conclusion. This innovative and engaging program was designed to emphasize on the need for a comprehensive and multidisciplinary approach in the management of diabetes in pregnancy. It is crucial for healthcare workers from all levels of hierarchy to work together and understand their contribution in successful management of this condition. This novel masterclass has realized this goal, and has great potential for integration into primary, secondary and tertiary healthcare systems.